Achieving high thermoelectric quality factor toward high figure of merit in GeTe. (August 2020) - Suwardi, A.; Cao, J.; Zhao, Y.; Wu, J.; Chien, S.W.; Tan, X.Y.; Hu, L.; Wang, X.; Wang, W.; Li, D.; Yin, Y.; Zhou, W.-X.; et al.
Abstract: In recent years, GeTe has received tremendous attention from the research community owing to its favorable electronic and thermal properties which make it one of the best performing thermoelectric compounds. In many reports, high performance has often been achieved via various doping/alloying methods, which typically involve more than one type of dopants. In contrast to the widely used codoping strategies, this work only uses a minute amount of 1% doping, giving rise to one of the highest quality factor (1.30) at 673 K amongst GeTe, with a corresponding zT of 1.5. The high performance is attributed to simultaneously improved electronic properties via carrier concentration optimization, as well as reduced thermal conductivity via additional phonon scattering brought about by In-mass fluctuations. More importantly, we elucidate on the importance of preserving the high quality factor via choosing the right dopants to optimize the carrier concentration. Furthermore, we showed that the strategy of evaluating the quality factor can be applied to other material systems, serving as a general guideline for thermoelectric materials design. The quality factor of GeTe in this work is superior to most other high-performing chalcogenides such as PbTe, SnTe, and SnS, revealing the large space for further enhancing its zT . Graphical abstract: Adding a minute amount of excess cation (1% Ge) and 1% In as a resonant dopant enhances the quality factor of GeTe, leading to a high zT of 1.5 at 673 K. Image 1 Highlights: An effective approach is used to optimize carrier concentration via cation-excess in GeTe. Indium doping in GeTe is used to modulate the quality factor. GeTe is amongst the binary chalcogenides with the highest quality factor. High quality factor is the key to enhance the figure of merit of GeTe from 0.8 to 1.5 at 673 K.